Study of carbonaceous fractions associated with indoor PM2.5/PM10 during Asian cultural and ritual burning practices. (September 2016) - Dewangan, Shippi; Pervez, Shamsh; Chakrabarty, Rajan; Watson, John G.; Chow, Judith C.; Pervez, Yasmeen; Tiwari, Suresh; Rai, Joyce
Abstract: The study was carried out to evaluate the seasonal and annual trend of thermal fractions (organic and elemental carbon) associated to different cultural/ritual-indoor aerosol carbonaceous matter compared to residential-indoors and ambient-outdoors. Thermal speciation of carbonaceous fractions (SCFs: OC1, OC2, OC3, OC4, OP, EC1, EC2, EC3) associated to cultural/ritual-indoors and indoor/outdoor relationship were also taken into account in four different types of cultural/ritual centers: 1) Marriage Places (MP), 2) Muslim Holy Shrines (MHS), 3) Buddhist Temples (BT), and 4) Hindu Temples (HT). Longitudinally measured 360 PM2.5 /PM10 samples throughout the year 2012–13, onto quartz fiber filters, were analyzed for organic (OC) and elemental carbon (EC) alongwith eight SCFs using thermal/optical reflectance/transmittance method. SCFs were determined in selected samples, representing all selected cultural/ritual-indoors, to address the source markers associated to biomass burning (BB) emissions; observed during cultural/ritual performances. Results have shown significantly higher levels of BB markers' SCFs in cultural/ritual-indoors compared those reported for residential-indoors and ambient-outdoors. Three to eight-fold higher carbonaceous aerosols was found in cultural/ritual-indoors compared to those determined in residential-indoors and ambient-outdoors. OC/EC ratio was found 2-fold higher in MHS and MP places compared to those found in other selected indoor and outdoor sites. Similarly, higher degree of seasonal variability with higher occurrence of aerosol fractions and associated OC and EC in winter is observed in both MHS and MP due to higher activity pattern. Highlights: The first report on assessment of indoor OC and EC in ritual places belong to major religions of Indian sub-continent, namely 1)Hindu Marriage places; 2)Muslim Holy Shrines; 3)Buddhist Temples; 4)Hindu Temples. Indoor OC and EC are found to be multi-fold higher levels compared to pure residential-indoors. Seasonal and temporal variation of indoor OC and EC has also been investigated. Outdoor infiltration, indoor generated itself and indoor/outdoor relationship for OC and EC data has been described in paper.